2007
DOI: 10.1152/ajpregu.00377.2007
|View full text |Cite
|
Sign up to set email alerts
|

Application of menthol to the skin of whole trunk in mice induces autonomic and behavioral heat-gain responses

Abstract: When ambient temperature is decreased in mammals, autonomic and behavioral heat-gain responses occur to maintain their core temperatures. However, what molecules in cutaneous sensory nerve endings mediate cooling-induced responses is unclear. Recently, transient receptor potential melastatin-8 (TRPM8) has been identified in cell bodies of sensory neurons as low-temperature and menthol-activated cation channel. We hypothesized that TRPM8 mediates cooling-induced autonomic and behavioral heat-gain responses. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
103
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(109 citation statements)
references
References 37 publications
5
103
1
Order By: Relevance
“…Contrary to Tajino et al, menthol did not cause any heat diffusion effect. 34) This might be because Tajino et al utilized an experimental setup, dosage, administration route, and ambient temperature that were different from those used in our study.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Contrary to Tajino et al, menthol did not cause any heat diffusion effect. 34) This might be because Tajino et al utilized an experimental setup, dosage, administration route, and ambient temperature that were different from those used in our study.…”
Section: Discussionmentioning
confidence: 83%
“…Consistently with these results, it has been reported that menthol causes hyperthermia. 33,34) Moreover, Ding et al showed that a potent TRPM8 agonist, icillin, causes hyperthermia in rats. 35) These results suggest that activation of TRPM8 induces thermogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, a series of recent in vivo studies using pharmacological antagonism and/or genetic deletion have established that TRPM8 plays a significant role in most individual thermoregulatory responses to cold: behavioral thermoregulation, BAT activation, peripheral vasoconstriction, and total metabolic response to cold (1,2,6,8,17,33). TRPM8 was also implicated in shivering thermogenesis in two studies using menthol as a TRPM8 agonist, which, however, were not conclusive due to possible TRPM8-independent actions of menthol (15,18,21,34). Despite this caveat, these and other studies seemed to have formed a prevailing implicit view in the literature that TRPM8 is a "universal" cold sensor, insofar as it controls every physiological response to cold.…”
Section: Discussionmentioning
confidence: 99%
“…However, in a cold environment (10°C), TRPM8-deficient mice exhibit reduced activation of BAT thermogenesis and lowered body core temperature compared with wild-type mice (165). Application of menthol, which activates TRPM8, to the skin of wild-type mice evokes warm-seeking behavior, as well as cold-defensive, physiological responses, including BAT and shivering thermogenesis and cutaneous vasoconstriction (166). These findings indicate that TRPM8 plays a role in the sensation of environmental cooling that is required for eliciting feedforward colddefensive responses.…”
Section: Peripheral Thermosensation For Body Temperature Regulationmentioning
confidence: 99%